PENGARUH PENGGUNAAN E-COMMERCE TERHADAP PENINGKATAN PENDAPATAN USAHA MIKRO KECIL DAN MENENGAH (Studi Kasus Pada UMKM Sektor Kuliner Di Kabupaten Bogor) - Fatimah Azzahra; Karuniana A. Dianta Sebayang; Dicky Iranto (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Internet users in Bogor Regency are increasing as infrastructure development progresses evenly. This began to affect the transaction habits between traders and buyers. Buyers who are starting to switch to online transactions, making MSME players try to keep up with new innovations in transactions through E-commerce platforms, so that the income they get is not problematic. This study aims to determine how much influence the use of E-commerce has on the increase in revenue obtained by MSME players in the culinary sector in Bogor Regency. The research method used in this research is descriptive method with qualitative analysis. Determination of the sample in this study using purposive sampling technique. The results showed that the use of E-commerce will be able to increase MSME revenues, marketed products will be more easily recognized by consumers making it easier to get customers. In addition, the use of E-commerce can save promotional costs and increase transaction speed and revenue. This will ultimately be able to increase competitiveness for MSMEs in the Bo Regency area.